Historical Paths and Intellectual Projects: The Case of Max Weber - Sven Eliaeson (Historicka Sociologie, 2017)
Max Weber is an elusive classic, and competing traditions claim his legacy. As in other cases, the interpretation of this classic should take into account formative experiences, historical context and links to older traditions. Weber theorized rational modernity, albeit with a certain ambiguity (the “iron cage”). He reworked the legacy of German historicism, but took it in the direction of methodological individualism; at the same time, and through the very affiliation to historicism, he contributed to German nation-building. His emphasis on the state as a necessary unit of analysis now seems obsolete, and so does his inclination to take the imperialistic dominance of the European great powers for granted. He was not immune to the ideology that opposed Germany’s cultural calling to Western civilization and Russian barbarism.